Vitamin D supplementation in pregnancy: a systematic review. - Harvey, N; Holroyd, C; Ntani, G; Javaid, K; Cooper, P; Moon, R; Cole, Z; Tinati, T; Godfrey, K; Dennison, E; Bishop, N; Baird, J; et al. (NIHR Journals Library, 2014)
BACKGROUND: It is unclear whether or not the current evidence base allows definite conclusions to be made regarding the optimal maternal circulating concentration of 25-hydroxyvitamin D [25(OH)D] during pregnancy, and how this might best be achieved. OBJECTIVES: To answer the following questions: (1) What are the clinical criteria for vitamin D deficiency in pregnant women? (2) What adverse maternal and neonatal health outcomes are associated with low maternal circulating 25(OH)D? (3) Does maternal supplementation with vitamin D in pregnancy lead to an improvement in these outcomes (including assessment of compliance and effectiveness)? (4) What is the optimal type (D2 or D3), dose, regimen and route for vitamin D supplementation in pregnancy? (5) Is supplementation with vitamin D in pregnancy likely to be cost-effective? METHODS: We performed a systematic review and where possible combined study results using meta-analysis to estimate the combined effect size. Major electronic databases [including Database of Abstracts of Reviews of Effects (DARE), Centre for Reviews and Dissemination (CRD), Cochrane Database of Systematic Reviews (CDSR) and the Health Technology Assessment (HTA) database] were searched from inception up to June 2012 covering both published and grey literature. Bibliographies of selected papers were hand-searched for additional references. Relevant authors were contacted for any unpublished findings and additional data if necessary. Abstracts were reviewed by two reviewers. INCLUSION AND EXCLUSION CRITERIA: SUBJECTS: pregnant women or pregnant women and their offspring. EXPOSURE: either assessment of vitamin D status [dietary intake, sunlight exposure, circulating 25(OH)D concentration] or supplementation of participants with vitamin D or food containing vitamin D (e.g. oily fish). OUTCOMES: offspring - birthweight, birth length, head circumference, bone mass, anthropometry and body composition, risk of asthma and atopy, small for gestational dates, preterm birth, type 1 diabetes mellitus, low birthweight, serum calcium concentration, blood pressure and rickets; mother - pre-eclampsia, gestational diabetes mellitus, risk of caesarean section and bacterial vaginosis. RESULTS: Seventy-six studies were included. There was considerable heterogeneity between the studies and for most outcomes there was conflicting evidence. The evidence base was insufficient to reliably answer question 1 in relation to biochemical or disease outcomes. For questions 2 and 3, modest positive relationships were identified between maternal 25(OH)D and (1) offspring birthweight in meta-analysis of three observational studies using log-transformed 25(OH)D concentrations after adjustment for potential confounding factors [pooled regression coefficient 5.63 g/10% change maternal 25(OH)D, 95% confidence interval (CI) 1.11 to 10.16 g], but not in those four studies using natural units, or across intervention studies; (2) offspring cord blood or postnatal calcium concentrations in a meta-analysis of six intervention studies (all found to be at high risk of bias; mean difference 0.05 mmol/l, 95% CI 0.02 to 0.05 mmol/l); and (3) offspring bone mass in observational studies judged to be of good quality, but which did not permit meta-analysis. The evidence base was insufficient to reliably answer questions 4 and 5. LIMITATIONS: Study methodology varied widely in terms of study design, population used, vitamin D status assessment, exposure measured and outcome definition. CONCLUSIONS: The evidence base is currently insufficient to support definite clinical recommendations regarding vitamin D supplementation in pregnancy. Although there is modest evidence to support a relationship between maternal 25(OH)D status and offspring birthweight, bone mass and serum calcium concentrations, these findings were limited by their observational nature (birthweight, bone mass) or risk of bias and low quality (calcium concentrations). High-quality randomised trials are now required. STUDY REGISTRATION: This study is registered as PROSPERO CRD42011001426. FUNDING: The National Institute for Health Research Health Technology Assessment programme.